Pengaruh Faktor Sumber Daya Manusia, Sarana dan Prasarana serta Dana Terhadap Ketersediaan Obat di Instalasi Farmasi RSUD Cibinong - Putri Reza Permana; Yaya Aria Santosa; Ahdun Trigono (SENTRI: Jurnal Riset Ilmiah, 2026)
The optimal availability of medicines is an important indicator in supporting the quality of healthcare services in hospitals. This study aims to analyze the influence of human resources (HR), facilities and infrastructure, as well as funding on the availability of medicines at the Pharmacy Installation of Cibinong Regional General Hospital (RSUD Cibinong). A quantitative approach was employed in this study, using a survey method through questionnaires distributed to 36 respondents consisting of pharmaceutical personnel. The data analysis technique used was multiple linear regression. The results of the study indicate that partially, human resources have a significant effect on drug availability with a regression coefficient of 0.328 and a significance of 0.035. Facilities and infrastructure also have a significant effect with a coefficient of 0.132 and a significance of 0.049. Meanwhile, funds are the most dominant variable with a regression coefficient of 0.447 and a significance of 0.000. Simultaneously, these three variables have a significant effect on drug availability, with a calculated F value of 25.415 and a significance of 0.000. The adjusted R² value of 0.531 indicates that these three variables together explain 53.1% of the variation in drug availability. This study concludes that improving the quality of human resources, optimal maintenance of facilities and infrastructure, and efficient and timely management of funds are important factors in strengthening the hospital pharmaceutical logistics system and ensuring sustainable drug availability. Furthermore, the availability of medicines influenced by these three factors directly impacts healthcare service outcomes and patient satisfaction by enabling timely access to essential treatments and reducing the risk of treatment delays.